A Study on the Online Shopping - Pre and Post Pandemic - Hasti Gada; Dhruvi Nandu; Nishi Shah; Niyati B Thakker (International Journal of Engineering and Management Research, 2023)
Prior to the pandemic, online shopping was infrequent. However, when the COVID-19 situation worsened, people were unable to purchase the products they needed since stores were closed and there was only one way to get them: online shopping. As a result, they started buying online, but they soon realized that they had a lot of possibilities, so they progressively went toward it. People continued to shop online and in-store as the situation stabilized. People preferred both online and in-store purchasing, but it was discovered that online shopping surged after the pandemic.